Respuesta del cultivo de lechuga (lactuca sativa l) a la aplicación de tres abonos líquidos a tres dosis en la zona de Pimampiro, Provincia de Imbabura. - Pineda Ortiz, Danny Roberto (2011)
The present investigation work one carries out in Mrs. Alba Navarrete's property, Sector Santa Rosa, Cantons Pimampiro, Provincials Imbabura. The area presents an altitude of 2450 msnm; temperature average 17º C; precipitation averages 600 yearly to 800 mm and humidity relative 66%. The texture is frank sandy; area of life dry forest, low montano and lightly alkaline pH 7.8 The used genetic material was the seed of lettuce variety big lakes (Great lakes 366). The studied treatments were liquid payments Biol (Fertilizer with the help of leguminous and fresh manure); Organic Power (organic Fertilizer liquidates) and Lonite (natural Fertilizer with the help of sour húmicos), with three different dose (1.5; 1.0 and 0.5 l/ha) applied to the 47, 62 and 77 days after the transplant. The design that you uses to evaluate the treatments was at random of complete blocks with 10 treatments and 4 repetitions. The variables were subjected to the variance analysis and to determine the level you significance among stockings of the treatments, the tukey test was applied to 5% of probability.